2005
DOI: 10.1159/000085620
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Paclitaxel in the Treatment of Advanced or Metastatic Breast Cancer Previously Treated or Not Treated with Docetaxel: A Phase II Study

Abstract: Background: Paclitaxel has been approved for 3-weekly administration in Japan. Recent reports suggest that weekly paclitaxel can achieve a higher tumor response and lower toxicity. Methods: This study was designed to investigate the usefulness and tolerability of weekly paclitaxel by 1-hour infusion in patients with metastatic breast cancer who were previously treated with docetaxel or other anticancer agents. Results: Thirty-five patients were enrolled. The overall response rate was 41.2% (14/34, 95% confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…However, PTX shifts the equilibrium toward microtubule assembly and stabilizes microtubules by preventing depolymerization [19]. As a result, PTX is reported to lack complete cross-resistance with DOC in several types of carcinomas [20][21][22]. Regarding ESCC, PTX monotherapy shows feasible efficacy, with an overall response rate of 44.2%, median duration of response of 4.8 months, and median OS of 10.4 months with manageable toxicity as a second-line regimen for patients previously treated with platinumbased chemotherapy [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, PTX shifts the equilibrium toward microtubule assembly and stabilizes microtubules by preventing depolymerization [19]. As a result, PTX is reported to lack complete cross-resistance with DOC in several types of carcinomas [20][21][22]. Regarding ESCC, PTX monotherapy shows feasible efficacy, with an overall response rate of 44.2%, median duration of response of 4.8 months, and median OS of 10.4 months with manageable toxicity as a second-line regimen for patients previously treated with platinumbased chemotherapy [5].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that weekly paclitaxel was effective in metastatic breast cancer with acceptable toxicity [23] , and therefore, it is conceivable that a paclitaxel and anthracycline combination could be an alternative to ET therapy. However, the previous study reported that the paclitaxel and doxorubicin combination had a higher incidence of cardiac failure.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, agents other than docetaxel should be considered for use in patients whose disease progresses within 1 year of receiving adjuvant therapy with docetaxel, although there is no widely accepted standard treatment. The results of several phase II studies have shown that weekly paclitaxel is modestly effective in patients with docetaxel-resistant MBC, with response rates of 20-41% and TTPs of 5.0-7.2 months [13][14][15].…”
Section: Patients Who Have Received Paclitaxel or Docetaxelmentioning
confidence: 99%